2017
DOI: 10.1017/s1047951117002062
|View full text |Cite
|
Sign up to set email alerts
|

Pulse therapy combined with oral corticosteroids in the management of severe rheumatic carditis and rebound

Abstract: The pulse therapy was effective in controlling severe rheumatic carditis and the oral corticosteroid prevented rebound episodes. Prolonged hospital stay was required for the clinical stabilisation of patients and to avoid the interruption of medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…18 On the other hand, a study by Torres et al found that combining pulse methylprednisolone and oral prednisolone appear to contribute to both reduced left chamber dimensions and prevention of rebound phenomenon. 19 A meta-analysis of the treatment of Group A streptococcus pharyngitis to prevent acute rheumatic fever concluded that there would be an approximately 60% reduction in cases of acute rheumatic fever if pharyngitis was appropriately treated, especially in endemic areas. 20 The large number of cases among the paediatric population underlines the need for more efforts in the public health sector for primary prevention, given the relative ease and low cost of Group A streptococcus pharyngitis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…18 On the other hand, a study by Torres et al found that combining pulse methylprednisolone and oral prednisolone appear to contribute to both reduced left chamber dimensions and prevention of rebound phenomenon. 19 A meta-analysis of the treatment of Group A streptococcus pharyngitis to prevent acute rheumatic fever concluded that there would be an approximately 60% reduction in cases of acute rheumatic fever if pharyngitis was appropriately treated, especially in endemic areas. 20 The large number of cases among the paediatric population underlines the need for more efforts in the public health sector for primary prevention, given the relative ease and low cost of Group A streptococcus pharyngitis treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The rebound phenomenon and rebound effects were observed after withdrawal of several drugs including beta blockers, corticosteroids, opioid drugs, antiepileptic, immunomodulatory and antidepressant agents (Fukuyama, Ganchingco, & Bäumer, 2017; Henssler, Heinz, Brandt, & Bschor, 2019; Koracevic et al., 2020; Torres, Torres, Torres, & Torres, 2018; Wilens, Zulauf, Ryland, Carrellas, & Catalina‐Wellington, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Application of remote sensing in rice has been increasing since mid 2000s with the MODIS sensors data (due to its easy access and with its higher temporal resolution or its ability to acquire the image every one or two days) and the main research objectives of rice remote sensing have been in retrieval and study of the rice characteristics such as Leaf Area Index (LAI), nitrogen and chlorophyll contents, biomass which have the guiding roles in the rice agronomic managements (Xu et al, 2022). The research publications are mostly seen from the developed nations that includes the United States of America (USA), China and Japan, but genuinely, the remote sensing has been boon in other nations as well for monitoring of rice crops mainly for the crop mapping (DDNS, 2016;Tiwari et al, 2021;Torres, 2022).…”
Section: A R T I C L E I N F Omentioning
confidence: 99%